2017
DOI: 10.1055/s-0036-1589089
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oxidation of Secondary Amines to N,N-Disubstituted Hydroxylamines by Choline Peroxydisulfate

Abstract: N,N-Disubstituted hydroxylamines were prepared directly from secondary amines by a reliable method using an oxidizing task-specific ionic liquid, choline peroxydisulfate. The operational simplicity, high selectivity, and green reaction conditions, make this method efficient and practical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Previous reports suggested that the oxidation impurity of ketamine was nitrogen oxidation impurity 31, which was synthesized via ionic liquid choline peroxydisulfate (ChPS). 14 However, this impurity was actually synthesized via Scheme 5. Side Reactions Involved in the Preparation of 5 hydrogen peroxide and oxidized in ethanol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports suggested that the oxidation impurity of ketamine was nitrogen oxidation impurity 31, which was synthesized via ionic liquid choline peroxydisulfate (ChPS). 14 However, this impurity was actually synthesized via Scheme 5. Side Reactions Involved in the Preparation of 5 hydrogen peroxide and oxidized in ethanol.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…During the forced degradation of ketamine hydrochloride using 3% H 2 O 2 and heating at 90 °C for 2 h, we found that the maximum oxidative degradation impurity was about 1.23%. Previous reports suggested that the oxidation impurity of ketamine was nitrogen oxidation impurity 31 , which was synthesized via ionic liquid choline peroxydisulfate (ChPS) . However, this impurity was actually synthesized via hydrogen peroxide and oxidized in ethanol.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In particular, unsymmetrical secondary hydroxylamines often require indirect syntheses, most often achieved by oxidation of a primary amine followed by alkylation. , In this context, methods based on the oxidation of amines are attractive and can provide access to secondary hydroxylamines in fewer steps. Indeed, secondary hydroxylamines have been synthesized via various oxidative methods (Scheme ), including the direct oxidation of secondary amines (Scheme A). , While reported procedures are direct, they often suffer from limitations, including poor chemoselectivity, overoxidation, narrow substrate scope, variable or low yields, or specialized or unstable reagents. Thus, alternative two-step sequences featuring an oxidation step are commonly employed, such as the oxidation of suitable tertiary amines followed by Cope elimination or oxidation of secondary amines with peroxide derivatives to form O -benzoyl hydroxylamines, which can then be cleaved under basic conditions (Scheme B) …”
Section: Introductionmentioning
confidence: 99%